Relationship between Adding Value, Trust and Job Satisfaction Based on Teachersâ Perceptions - Talebloo, Baharak; Kasmaienezhadfard, Sara; Pourrajab, Masoumeh; Roustaee, Roya; Bin Basri, Ramli (Journal of Educational, Health and Community Psychology, 2015)
AbstractÂ The aim of this study is to determine the relationship between adding value; trust and teacher satisfaction among primaryand secondary school teachers in Malaysia.In this research,375 teachers were selected based on convenience random sampling from teachers who study in educational field. This study is quantitative research and data were collected based on questionnaire and were analyzed using descriptive, correlation and regression analysis. Based on Pearson Product-Moment Correlation Coefficient the results show that the high significant relationship exists between trust and teacher job satisfaction. However, low and negative relationship was found to exist between adding value and teacherâs satisfaction. Regarding to multiple regression, there are significant contribution of trust and teacher satisfaction. However, just adding value was not increase teacherjob satisfaction.Â Key words: Adding value âJob Satisfaction -Trust -Primary school- Teachers-Malaysia.